Simulation-based inference captures non-Markovian effects as exemplified in protein production kinetics through cell division - Pedro Pessoa; Juan Andres Martinez; Vincent Vandenbroucke; Frank Delvigne; Steve Pressé (Proceedings of the National Academy of Sciences, 2026)
Inferring protein production kinetics in dividing cells is complicated by protein inheritance from the mother cell. For instance, fluorescence measurements commonly used to assess gene activation may reflect not only newly produced proteins but also those inherited through successive cell divisions. In such cases, observed protein levels in any given cell are shaped by its division history. As a case study, we examine the activation of the glc3 gene in yeast involved in glycogen synthesis and expressed under nutrient-limiting conditions. We monitor this activity using snapshot fluorescence measurements via flow cytometry, where green fluorescent protein (GFP) expression reflects glc3 promoter activity. A naïve analysis of flow cytometry data ignoring cell division suggests many cells are active at low expression levels. Explicitly accounting for the (inherently non-Markovian) effects of cell division and protein inheritance makes it impossible to write down a tractable likelihood, namely the probability of observing data given a model—a key ingredient in physics-inspired inference. The dependence on a cell’s division history breaks the assumptions of standard (Markovian) master equations, rendering traditional likelihood-based approaches inapplicable. In order to generate a method for inference in arbitrary non-Markovian dynamics, we adapt conditional normalizing flows (a class of neural network models designed to learn probability distributions) to approximate otherwise intractable likelihoods from simulated data. In doing so, we find that glc3 is mostly inactive under stress, showing that while cells occasionally activate the gene, expression is brief and transient.